"How can we leave the traditions of our Baab Daada" socio‐cultural structures and values driving menstrual hygiene management challenges in schools in Pakistan. (2nd September 2019) - Mumtaz, Zubia; Sivananthajothy, Priatharsini; Bhatti, Afshan; Sommer, Marni
ABSTRACT: Introduction: Despite the growing attention to the relationship between menstruation and girls schooling, there remain many challenges to addressing the issue. Current interventions, which mostly focus on developing WASH infrastructure and sanitary hygiene management products, while necessary, may not be sufficient. This paper aimed to identify the root causes of poorly maintained WASH infrastructure, and understand the deeply embedded socio‐cultural values around menstrual hygiene management that need to be addressed in order to provide truly supportive school environments for menstruating girls. Methods: Qualitative data were collected in rural and urban sites in three provinces in Pakistan using participatory activities with 312 girls aged 16–19 years, observations of 7 School WASH facilities, 42 key informant interviews and a document review. Results: Three key themes emerged from our data: (1) a poorly maintained, girls‐unfriendly School WASH infrastructure was a result of gender‐insensitive design, a cultural devaluation of toilet cleaners and inadequate governing practices; (2) the design of WASH facilities did not align with traditionally‐determined modes of disposal of rag‐pads, the most common used absorbents; (3) traditional menstrual management practices situate girls in an 'alternate space' characterised by withdrawal from many daily routines. These three socio‐culturally determined practices interacted in a complex manner, often leading to interrupted class engagement and attendance. Conclusions: To be truly effective, current menstrual hygiene management strategies need to address the root causes of poor WASH infrastructure and ensure facility design is sensitive to the gendered and deeply embedded local socio‐cultural values and beliefs around menstrual hygiene management.